Linguistic insecurity and the linguistic ownership of English among Singaporean Chinese - Foo, Amanda Limin (2021)
Linguistic insecurity and linguistic ownership rest on the same foundational ideas. However, despite the extensive study of both, the two concepts have never been discussed in conjunction. This paper refines both concepts and puts forth a set of conditions to test for the presence of linguistic insecurity and the exercise of linguistic ownership in 287 Singaporeans through an empirical survey examining their use of English, as well as their perceptions of other speakers in the Singapore English-speaking community and Singapore English itself. The results reveal that Singaporeans are linguistically insecure but yet exercise full ownership of the English language. These somewhat paradoxical findings uncover an unusual relationship between linguistic insecurity and ownership. We argue in this paper that there exists a new type of linguistic ownership in Singapore, one that does not invoke notions of authority or legitimacy. It is this new notion of linguistic ownership that drives a new brand of linguistic insecurity documented in this paper.